Towards a distributed and operational pelagic imaging network - Rainer Kiko; Rubens M. Lopes; Y. Dodji Soviadan; Lars Stemmann (Ocean and Coastal Research)
Dimensions of particulate matter found in the water column of marine and freshwater environments (the pelagic realm) range from nanometers to tens of meters. Included in this enormous size range are miniature bacteria, phytoplankton (photosynthetic microalgae), mixoplankton (mixotrophic microorganisms), micro- to meter sized drifting animals (zooplankton), plastic particles, detrital aggregates and fecal pellets, fish, whales and many others. These particles and organisms are involved in many different processes and perform a multitude of services, such as in oceanic biogeochemistry (carbon fixation, oxygen production, carbon export and others) or human nourishment (fisheries). Digital optical tools used in pelagic imaging approaches now allow to bridge this enormous size span and to image micro- to meter-sized objects in situ or on discrete samples. Monitoring plankton, nekton, and particle dynamics at spatial and temporal scales that enable effective management of marine and freshwater environments poses a collective challenge for society. We here argue that a global, distributed and operational network for pelagic imaging is needed and within reach, and we provide recommendations how it can be attained via the voluntary activities of the pelagic imaging community and strategic support from funding agencies and other stakeholders.